The Ecuadorian State in the southeastern frontier: a creation based on affection, 1893-1964 - Cecilia Ortiz-Batallas (Íconos)
This article examines the state and nation-building process in Southeast Ecuador (in what is now the Morona-Santiago province) during the first half of the XXth century. This territory – which was originally settled by the Achuar and Shuar peoples- remained in dispute between Ecuador and Peru since the day Ecuador became an independent country in 1830, and until 1998, when the two nations reached a final agreement on their common borders. Given the fledgling condition of the Ecuadorian state in the period under study, the information that can be obtained from bureaucratic and official sources is scanty. Thus, a different approach to data gathering had to be undertaken. It is argued that in those remote frontier territories, the Salesian missionaries became the actual and real proxy of the central government as well as of other external powers: the House of Don Bosco and the Vatican. Specific attention is given to the ways in which authority is endowed with meaning as a result of the efforts of actors to make sense of affections and disaffections, hopes, emotions, violence, disappointments and fear, which are to be seen as the founding components of colonialist domination processes. The arguments are supported in documentary sources, and- crucially- on the versions provided the participants in some of the recounted events. In this scene, the Shuar people is not seen as a passive actor. Instead, it displays its ability to negotiate with the power-originated messages of domination.